FAMILY PIPUNCULIDAE - Rafael, José Albertino; Rodriguez, Hugo Cesar (Zootaxa, 2016)
Pipunculidae presently have around 1,400 known species, but it is poorly known in Colombia, with only ten reported species in all territory. The genera Eudorylas Aczél and Tomosvaryella Aczél are the most abundant. This work provides information on the species distribution. No endemic genera have been recorded to date from Colombia.